A variety of potato cultivars from the VIR World Collection in northern conditions - T. E. Zhigadlo (Овощи России, 2024)
Relevance. Potatoes are one of the most popular agricultural crops in Russia. The unique chemical composition characterizes potatoes as a valuable food product in the diet of the population. One of the important factors for increasing and stable potato yields is the selection of the optimal assortment for each region of the Russian Federation. Therefore, the varieties most adapted to local growing conditions should be used in production. The world potato collection allows solving various issues of modern breeding, such as: early maturity, resistance of tubers to various diseases, seed quality, adaptation to climatic stresses, history and systematics. The study and evaluation of new potato breeding varieties makes it possible to identify promising source material for the creation of future varieties suitable for cultivation in the northern regions of the country.The purpose of this study is to characterize the studied potato samples in extreme climate conditions.Material and methodology. In 2013-2023, 543 potato samples from the World Collection of VIR were studied at the experimental field of the Polar Experimental Station VIR branch according to the main biological and economically valuable characteristics. For a comprehensive assessment of the varieties according to the main economic and biological characteristics, phenological observations were carried out, the harvest was taken into account during early and final harvesting, including the structure of the crop. Visual assessment of diseases was carried out in the field and during storage. Starch was determined in the laboratory. All basic accounting is performed according to the VIR methodology.Results and discussion. Over the years, 15 potato varieties with the best characteristics of economically valuable traits have been identified. According to the results of the final harvest, 6 varieties had a stable harvest – Favorit, Meteor, Tekes, Severny, Gusar, Lingonberry. The yield of these varieties was 1034-1409 g/bush.